1989
DOI: 10.1016/0035-9203(89)90644-5
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal flora of patients with megaoesophagus secondary to Chagas disease

Abstract: The jejunal flora of 15 patients with megaoesophagus secondary to Chagas disease was studied and compared with that of 15 control individuals. In addition to the serological reactions for Chagas disease (immunofluorescence and complement fixation reaction), all subjects were submitted to endoscopy and X-ray of the oesophagus, gastric secretory study and investigation of the jejunal flora. The mean bacterial counts (log10) of Chagas disease patients (4.14 +/- 2.15 c.f.u./ml) was significantly higher than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…For the stomach, duodenum, jejunum (proximal and distal), and proximal ileum, similar methods were used. [19][20][21][22] Finally, samples from the distal ileum, colon, and rectum were collected using a new method developed by the authors. 28 The oral cavity presented very diverse microbiota due to the different anatomical sites and constant exposure to the external environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the stomach, duodenum, jejunum (proximal and distal), and proximal ileum, similar methods were used. [19][20][21][22] Finally, samples from the distal ileum, colon, and rectum were collected using a new method developed by the authors. 28 The oral cavity presented very diverse microbiota due to the different anatomical sites and constant exposure to the external environment.…”
Section: Discussionmentioning
confidence: 99%
“…46 This method was tested in our midst by Machado et al, 19 who collected samples of the jejunum liquid in patients suffering from Chagasic achalasia. It was also used by Quintanilha et al 20,21 for qualitative evaluation of microbiota alterations in the proximal jejunum of patients with Chagasic megacolon, both before and after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 The bacterial concentration was expressed in units of colony formation per milliliter (UCF/ml), expressed in logarithm base 10 (Log 10 )…”
Section: Methodsmentioning
confidence: 99%
“…In fact, hyperproliferation of aerobic bacteria and the presence of anaerobic bacteria in the small bowel have been documented in patients with Chagasic megaesophagus and/or megacolon, with the number of colonies being as high in some cases as those occurring in patients with the clinical syndrome of bacterial overgrowth in the small bowel 29 30 51 . Since the participation of changes in gastric secretion was excluded, the abnormality was attributed to disorders of local motility 30 . In support of this hypothesis, it was observed that two cases of Chagasic megajejunum with clearly detectable alterations upon manometry and with confirmed bacterial overgrowth in the small bowel developed the typical clinical syndrome of bacterial overgrowth (chronic diarrhea, evidence of malabsorption and improvement with antibacterial treatment) 9 .…”
Section: Figure 1 -Recordings Of Fasting Small Intestine Motility In mentioning
confidence: 99%